How can students be supported by ChatGPT as a tutor in hands-on chemistry education? - Fox, Marvin Lee; Peeters, Hendrik; Fechner, Sabine (Conference of The European Science Education Research Association (ESERA))
Keywords: Artificial intelligence; education; chemistry

Prompting bei AR-gestütztem Experimentieren im Chemieunterricht - Peeters, Hendrik; Habig, Sebastian; Fechner, Sabine (Jahrestagung der Gesellschaft für Didaktik der Chemie und Physik e.V. (GDCP))

Harnessing temporal dispersion for integrated pump filtering in spontaneous heralded single-photon generation processes - Brockmeier, Julian; Schapeler, Timon; Lange, Nina Amelie; Höpker, Jan Philipp; Herrmann, Harald; Silberhorn, Christine; Bartley, Tim (New Journal of Physics)

Virtual Reality trifft Künstliche Intelligenz. KI unterstützt bei virtueller Praktikumsvorbereitung - Peeters, Hendrik; Hansel, Jan-Luca; Graute, André; Fischer, Matthias; Weinberger, Christian; Neiske, Iris; Fechner, Sabine (Laborpraxis)

Thematic Working Group 2 - Developing and leading digital learning cultures in schools: the role of leadership - Tan, Seng Chee; Phillips, Mike; Chammon, Jacob; Cochrane, Janet; Eickelmann, Birgit; Kral, Marijke; Medagedara, Peiris; Pangeni, Shesha Kanta; Murtagh, Karen; Kilcoyne, Anthony (Designing Education Ecosystems for the Future: The Role of Digital Technologies. Report of EDUsummIT 2025 (eBook))

Thematic Working Group 4 - Professional digital competence of teachers: leveraging digital technologies to deepen learning - Prestridge, Sarah; Prasse, Doreen; Bescherer, Christine; Bruillard, Eric; Charania, Amina; Drossel, Kerstin; Friesen, Sharon; Ge, Xun; Jacobsen, Michele; Kafyulilo, Ayoub; Morren, Milou; Moynihan, Denis; et al. (Designing Education Ecosystems for the Future: The Role of Digital Technologies. Report of EDUsummIT 2025 (eBook))

Solvolytically debondable adhesive systems – potentials and challenges for repair and recycling - Gilich, Julian; Kroos, Janika; Teutenberg, Dominik; Meschut, Gerson (The Journal of Adhesion)
In the context of decarbonization initiatives, the repairability and recyclability of components have become a major concern in various industrial sectors, particularly for resource-intensive components. The development of innovative bonding and debonding processes that must adhere to the stringent mechanical specifications of the manufacturers and facilitate their efficient disassembly is a major issue faced in the implementation of a sustainable circular economy. Although adhesively bonded joints satisfy the stringent requirements for mechanical performance, they present several challenges during the repair and recycling process. Solvolytically debondable epoxy resin adhesives may be employed to overcome this issue. In this study, we aim to conduct an exploratory feasibility study on the application of such chemical debonding mechanisms within an adhesive bond as well as to systematically analyse and evaluate the suitability of such adhesive systems for various applications. To this end, we employed various thermo-analytical methods and quasi-static tensile tests to characterise the mechanical adhesive and joint properties of two solvolytically debondable adhesive systems. Furthermore, we analysed the debondability of the adhesive joints and evaluated their feasibility in an industrial environment. The results indicate considerable application potential for solvolytically debondable adhesives, along with further development steps currently required.

Christologie der Beziehung – Begegnungen mit Frauen im Markusevangelium - Breuer, Saskia; Taschl-Erber, Andrea (Personale Christologie)

Christologie der Beziehung - Begegnungen mit Frauen im Markusevangelium - Breuer, Saskia Rebecca; Taschl-Erber, Andrea (Personal Christology)

Diskriminierungssituationen im Praxissemester aus Sicht von Lehramtsstudierenden - Truong, Ha My; Vogelsang, Christoph
Diskriminierungserfahrungen können sich negativ auf die Kompetenzentwicklung von Schülerinnen und Schülern auswirken, was wiederum Bildungsungerechtigkeit zur Folge haben kann (Hummrich, 2023). Um solchen Dynamiken frühzeitig entgegenzuwirken soll in der Lehrkräfteausbildung, nach den Standards der Kultusministerkonferenz (KMK) auch der reflektierte Umgang mit Diskriminierung gefördert werden: „Die Absolventinnen und Absolventen […] analysieren Konflikte und kennen Methoden der konstruktiven Konfliktbearbeitung sowie des Umgangs mit Gewalt und Diskriminierung“ (KMK, 2019, S.10). Ein wichtiger Bestandteil der universitären Phase ist das Praxissemester (PS), das in NRW ein fünfmonatiges Schulpraktikum umfasst. Obwohl sich bereits einige Studien mit Diskriminierungserfahrungen an Schulen (z.B. Höhl, 2021; Ziemes, 2024) und in der Lehrkräfteausbildung (Fereidooni, 2015) auseinandersetzten, gibt es bislang keine quantitative Studie, die die Perspektive von Lehramtsstudierenden im PS systematisch einbezieht. An der Universität Paderborn wurde daher in einer explorativen Querschnittsbefragung (N=431) erfasst, inwiefern Lehramtsstudierende Diskriminierungssituationen im Praxissemester beobachten und wie sie ihre Kompetenzen im Umgang mit Diskriminierung in der Schule einschätzen. In den Ergebnissen zeigt sich, dass die Studierenden das Differenzmerkmal Migrationshintergrund mit 31% in den beobachteten Fällen als Diskriminierungsgrund nannten. Zudem nahmen sie wahr, dass am häufigsten die Schüler*innen untereinander abwertend über andere Mitschüler*innen sprachen. Dies kam bei 67% der Befragten mindestens einmal im PS vor. Bei den Studierenden selbst haben 11% mindestens einmal im PS Diskriminierung durch Lehrkräfte erfahren und mit 14% wurden sie mindestens einmal von Schüler*innen diskriminiert. Die Studierenden hielten sich aber überwiegend für ausreichend kompetent im Umgang mit Diskriminierungssituationen.

Diskrimierungserfahrungen im Praxissemester - Truong, Ha My

The quality of digital curriculum resources for mathematics in German educational policy - Rezat, Sebastian (ZDM – Mathematics Education)
This paper examines the governance and quality control of digital curriculum resources (DCR) for K-12 mathematics education in Germany. It focuses on approval processes and criteria set by the 16 federal states, arguing that these have the potential to influence the development of DCR. Using qualitative content analysis, the study explores three research questions: which DCR require official approval, the criteria applied for approval, and the extent to which these criteria are mathematics-specific. Findings indicate that 10 federal states maintain official approval systems, covering digital equivalents of printed textbooks and selected supplemental materials. However, most DCR fall outside these regulated processes, leaving their evaluation largely to individual schools and teachers. The study identifies 17 categories of quality criteria, but reveals a lack of detailed, mathematics-specific requirements. Instead, many criteria are broad references to didactical principles and educational goals, leaving the interpretation and application of these quality standards open-ended. Subject-specific criteria are included but remain limited in specificity. The study underscores the need for research-informed, mathematics-specific quality standards to guide DCR development and approval, emphasizing their importance amidst challenges like artificial intelligence. Policymakers are urged to adopt clearer criteria to ensure high-quality DCR to be used in schools.
Keywords: governance; digital curriculum resources; digital textbooks; digital curriculum materials; quality

Generation time for biexact functors and Koszul objects in triangulated categories - Letz, Janina Carmen; Stephan, Marc (Doc. Math.)

Koszul homomorphisms and universal resolutions in local algebra - Briggs, Benjamin; Cameron, James C.; Letz, Janina Carmen; Pollitz, Josh (Forum Math. Sigma)

An equivalence linking CM-types $A_∞$ and $D_∞$ - Cummings, Charley; Gratz, Sira; Kirkman, Ellen; Letz, Janina Carmen; Rock, J. Daisie; Špenko, Špela

Regular sequences for triangulated categories - Kekkou, Antonia; Letz, Janina Carmen; Stephan, Marc

Realization functors in algebraic triangulated categories - Letz, Janina Carmen; Sauter, Julia (Abh. Math. Semin. Univ. Hambg.)

Tensor extriangulated categories - Bennett-Tennenhaus, Raphael; Goodbody, Isambard; Letz, Janina Carmen; Shah, Amit (J. Algebra)

Transfer of A-infinity structures to projective resolutions - Letz, Janina Carmen (Comm. Algebra)

The Rouquier dimension of the category of perfect complexes over a regular ring - Letz, Janina Carmen